2011
DOI: 10.1016/j.burns.2011.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of race and neighborhood on the risk for and outcomes of burns in the elderly in North Carolina

Abstract: Risk factors for mortality and length of hospital stay in elderly burn patients are well established, but the influence of race and socioeconomic status has not been evaluated. This study evaluates the effect of neighborhood level socioeconomic indicators on burn injury risk determines whether race and neighborhood influence burn injury outcomes in the elderly. Data from the North Carolina Jaycee Burn Center was linked to United States Census Bureau block group socioeconomic data. The odds of death and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…Not all SES constructs are equally attributable to injury risk. We found that the likelihood of injury was more strongly associated with measures of relative poverty when measured in conjunction with the level of education, 31 32 40 but not when measured using median income. 32 40 Employment-related variables were more indicative of unintentional rather than intentional injury.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Not all SES constructs are equally attributable to injury risk. We found that the likelihood of injury was more strongly associated with measures of relative poverty when measured in conjunction with the level of education, 31 32 40 but not when measured using median income. 32 40 Employment-related variables were more indicative of unintentional rather than intentional injury.…”
Section: Discussionmentioning
confidence: 67%
“…Two measures were variations on an area's proportion of lone parent families. 11 29 30 32 39 40 Other constructs included the ‘proportion of men’, 37 the ‘proportion of population ages 59 years or older’ 40 and the proportion of population having moved in the past 5 years. 31 Each measure was statistically significantly associated with injury when evaluated in pairwise comparisons or when aggregated into a composite index.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Although aging in place is preferable to many older adults, the elderly are at a disadvantage when it comes to home fire safety (HFS) and are at increased risk for burns. 3,4 Fire prevention education has historically been focused on reaching school-aged children, and it has only been more recently that fire services/ departments have recognized older adults as a high risk population for home fires, making this a new focus in fire prevention. 2,3,5e8 Much of the research addressing HFS in the older adult population has centered on risk factors associated with fire and burn injuries.…”
Section: Introductionmentioning
confidence: 99%